The distributional consequences of tax reforms under market distortions - Konstantinos Angelopoulos; Wei Jiang; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2011)
In this paper we examine the importance of imperfect competition in product and labour markets in determining the long-run welfare effects of tax reforms assuming agent heterogeneity in capital holdings. Each of these market failures, independently, results in welfare losses for at least a segment of the population, after a capital tax cut and a concurrent labour tax increase. However, when combined in a realistic calibration to the UK economy, they imply that a capital tax cut will be Pareto improving in the long run. Consistent with the theory of second-best, the two distortions in this context work to correct the negative distributional effects of a capital tax cut that each one, on its own, creates.
Keywords: E24; E62; 330; market imperfections; heterogeneous agents; unemployment; tax reform